The Effects of Clove Oil in Color Changes and Zooxanthellae Density on Porites lobata - Rahim, Sri Wahyuni; Nessa, M. Natsir; Trijuno, Dody D; Djawad, M. Iqbal (Journal of Indonesian Coral Reefs, 2012)
Destructive fishing such as using cyanide in capture of ornamental fish has caused damage to the coral reefs, this is suggested the use of clove oil which considered eco-friendly fishing. This study aims to analyze the changes of color, zooxanthellae density and mitotic index of coral Porites lobata after exposure to several concentrations of clove oil. Experimental design was a factorial design, which consists of six concentrations and five time treatments with 3 replication. Coral was placed into the 1.0x0.5x1.0 m aquarium that contains clove oil solution in different concentrations (control, 20, 30, 40, 50, and 60 ppm) for 5 min and then transferred to a tank containing clean seawater for 60 seconds and then removed to tanks for the recovery process. Observation was made everyday for coral color changes in 17 days period and on day 1, 5, 9, 13 and 17 for zooxanthellae density and mitotic index.Â  The results showed that the were no changes in Porites lobata colors until the 17th day after exposure to 20Ã¢â¬â60 ppm of clove oil and there was no significant difference in the zooxanthellae density and mitotic index of the Porites lobata on concentration variation, while zooxanthellae densities and mitotic index showed significant difference on time (day) variation. This suggested that exposure to clove oil atÂ  a concentration of 20Ã¢â¬â60 ppm did not affect the color change, zooxanthellae density and mitotic index of Porites lobata.